Laparoscopy in the diagnosis of tuberculosis in chronic pelvic pain. Issue 3 (September 2016) - Rajaram, Shalini; Gupta, Priyanka; Gupta, Bindiya; Kaur, Iqbal R.; Goel, Neerja
Abstract: Background : To estimate the prevalence of genital tuberculosis in women with idiopathic chronic pelvic pain on laparoscopy, correlate laparoscopic findings with microbiological and histological diagnosis of tuberculosis and assess the response to anti tubercular treatment (ATT) in these cases. Method : In a prospective cohort study, fifty women with idiopathic chronic pelvic pain were enrolled. Diagnostic laparoscopy was done in all women and fluid from pouch of Douglas and/or saline washings were sent for acid fast bacilli (AFB) smear, conventional and rapid culture and DNA polymerase chain reaction (PCR) analysis for diagnosis of genital TB. The results of these tests were analyzed and agreement with laparoscopy was assessed using Kappa statistics. Pain scores using visual analogue scale were compared before and after treatment. Results : Pelvic pathology was present in 44 (88%) women of idiopathic chronic pelvic pain, with a 34% prevalence rate of genital tuberculosis. Pelvic inflammation was associated with positive peritoneal fluid PCR ( n  = 4) and AFB culture ( n  = 3). Acid fast bacilli PCR had substantial agreement (kappa statistics = 0.716) with visual findings at laparoscopy. There was a significant reduction in pain scores after treatment. Conclusion : Genital tuberculosis contributes to one-third cases of chronic pelvic pain. Pelvic inflammation is an early feature of genital TB and peritoneal fluid PCR has the best co-relation with laparoscopic findings of genital tuberculosis.